A Study on the Client Perceptions of Services Offered by SBI Factors (coimbatore) - Srividya, V. (Indian Journal of Marketing, 2005)
The Indian financial market is under dynamic transformation with many new financial products and delivery systems being experimented with. Besides catering to the capital and money market some of these innovative products are aimed at providing an alternative avenue towards meeting the financial needs of a specific clientele for their working capital. Till the early nineties commercial banks were the most important source for the working capital needs of the industries. Even now bank finances in the form of loans, cash credits, overdrafts, purchasing and discounting of bills and FCNR (B) loans play a dominant role in meeting the short term needs of the industry, however they have their own limitations. To overcome the limitation innovative financial products were sought. One such product is factoring which, though not to be taken as a panacea for all organizational ills, can substantially reduce the effects of the same and help the small scale sector to tide over at least some of the problems to a reasonable extent.